Characteristics and risk factors for renal recovery after acute kidney injury in critically ill patients in cohorts of elderly and non-elderly: a multicenter retrospective cohort study - Xiujuan Zhao; Chengjian Li; Yunwei Lu; Shu Li; Fuzheng Guo; Haiyan Xue; Zhenzhou Wang; Yulan Jiang; Shaoguang Liu; Mingming Chai; Tonghai Du; Fengxue Zhu (Renal Failure)
Background The purpose of this study was to explore the risk factors for renal nonrecovery among elderly and nonelderly patients with acute kidney injury (AKI) in critically ill patients.Methods A multicenter retrospective cohort of 583 critically ill patients with AKI was examined. We found the best cutoff value for predicting renal recovery by age was 63 years old through logistic regression. All patients were divided into two cohorts, age <63 and age ≥63-years old; on the basis of renal recovery at 30 days after AKI, the two patient cohorts were further divided into a renal recovery group and a renal nonrecovery group. Multivariate logistic regression was used to analyze the risk factors affecting renal recovery in the two cohorts.Results The 30-day renal recovery rate of patients aged <63 years was 70.0% (198/283), multivariate analysis showed that the independent risk factors affecting renal nonrecovery in age <63 years old included AKI stage, blood lactate level and hemoglobin level. The 30-day renal recovery rate of patients aged ≥63 years was 28.7% (86/300), multivariate analysis showed that the independent risk factors for renal nonrecovery in age ≥63-years old included diabetes mellitus, surgery with general anesthesia, AKI stage, APACHE II score, eGFR, and hemoglobin level.Conclusions The renal nonrecovery after AKI in critically ill patients in patients aged ≥63 years was more strongly affected by multiple risk factors, such as diabetes mellitus, surgery with general anesthesia, eGFR, and APACHE II score, in addition to hemoglobin and AKI stage.